Practices of restitution : law and aesthetics in modern Germany / Laura Petersen, University of Lucerne. - Petersen, Laura E. (Law in context., 2026)
Since the end of the Second World War, restitution in Germany - Wiedergutmachung - has been mainly understood as part of state or private law. This book offers a different approach, arguing that authors and artists have also taken up a responsibility for restitution. Deploying the literal translation 'making-good-again', this book focuses on the 'making' of law, literature and visual art to argue that restitution is a practice which is found in different genres, sites and temporalities. The practices of restitution identified are dynamic, iterative and incomplete: they are practices of failure. Nevertheless, in this book, the question of how to conduct restitution emerges as a material question of responsibility asked through the making of texts and objects in different genres, including law. The resulting text is a unique expansion and re-conceptualisation of the practices of jurisprudence, restitution and responsibility in the context of the aftermath in Germany. This title is also available as open access on Cambridge Core.